2019
DOI: 10.1016/j.tipsro.2018.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Are radiation oncologists following guidelines? An audit of practice in patients with uncomplicated bone metastases

Abstract: Background: Best-practice guidelines recommend single-fraction (SFRT) instead of multi-fraction radiation therapy (MFRT) for uncomplicated symptomatic bone metastases. SFRT is comparable to MFRT in relieving pain, convenient for patients, and cost-effective. Patterns of practice in Canada reveal that SFRT is underused, with significant variability across the country. We audited SFRT use and studied factors that may influence treatment decisions at a large academic tertiary care center in Quebec, Canada. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 41 publications
(65 reference statements)
0
7
0
Order By: Relevance
“…As previously mentioned, other studies have shown increased use of SFRT in patients with worse performance status. 24,25 Unfortunately we are unable to confirm these results due to lack of available data in our series. Finally, ROs dedicated to palliative RT prescribed SFRT significantly more frequently than their peers.…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…As previously mentioned, other studies have shown increased use of SFRT in patients with worse performance status. 24,25 Unfortunately we are unable to confirm these results due to lack of available data in our series. Finally, ROs dedicated to palliative RT prescribed SFRT significantly more frequently than their peers.…”
Section: Discussionmentioning
confidence: 67%
“…Similar primary tumor-related differences were observed in other studies. For example, even in the study by Di Lalla et al, 25 lower SFRT rates were recorded in breast cancer patients. As previously mentioned, other studies have shown increased use of SFRT in patients with worse performance status.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations